2017
DOI: 10.4067/s0718-07642017000100003
|View full text |Cite
|
Sign up to set email alerts
|

Producción de Diésel Renovable a partir de Aceite de Higuerilla mediante Catalizadores de Níquel-Molibdeno Soportados sobre Alúmina

Abstract: ResumenSe sintetizaron dos catalizadores tipo Ni-Mo soportados sobre -Al2O3, con diferentes contenidos másicos de los metales activos, y su actividad catalítica en el proceso de desoxigenación de aceite de higuerilla fue evaluada y comparada con el desempeño obtenido con un catalizador comercial. Previo a las reacciones de desoxigenación, los catalizadores fueron reducidos y sulfurados con H2S producido in-situ. Los catalizadores fueron caracterizados mediante DRX, adsorción-desorción de N2 a 77 K, XRF y TPR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Although in recent years many studies have been published about HDT of vegetable oils, a limited number of them have reported the HDT of castor oil or its fatty acid methyl esters (FAMEs) for renewable diesel production . Only recently, Orozco et al described the selective production of green diesel from castor oil in a continuous‐flow fixed‐bed microreactor using a commercial sulfided NiMo/Al 2 O 3 without promoting hydrocracking (HDC) reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Although in recent years many studies have been published about HDT of vegetable oils, a limited number of them have reported the HDT of castor oil or its fatty acid methyl esters (FAMEs) for renewable diesel production . Only recently, Orozco et al described the selective production of green diesel from castor oil in a continuous‐flow fixed‐bed microreactor using a commercial sulfided NiMo/Al 2 O 3 without promoting hydrocracking (HDC) reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Meller et al 13 reported the deoxygenation of castor oil-derived fatty acid methyl esters in a batch process at 340 °C, 25 bars H 2 pressure for 6 h of reaction and reported a C 17 yield of 87.0 wt % and a C 18 yield of 9.0 wt % using a Pd/C catalyst. Finally, Sańchez et al 14 reported the hydrotreatment of castor oil with a complete conversion and C 17 and C 18 yields of 54.4 and 20.9 wt %, respectively, using NiMo/Al 2 O 3 in a batch process at 350 °C and 90 bars of H 2 pressure for 4 h of reaction. As can be understood, none of the studies developed a catalyst or established a set of reaction conditions specifically tailored to enhance selectivity toward the HDO pathway over the decarboxylation/decarbonylation pathway, which is a key gap that this study aims to bridge.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Según la directiva 2003/30/CE de la Comisión de la Unión Europea, se sugiere el uso de biocombustibles para asegurar y diversificar la oferta de energía, y a su vez, disminuir las emisiones netas de CO2 para el transporte terrestre en Europa. El biodiésel se define como los mono ésteres de alquilo de ácidos grasos obtenidos a partir de recursos renovables tales como aceites vegetales, grasas animales, aceites residuales y aceite de algas (Malhotra y Sarin, 2004;Sánchez et al, 2017). Se estima que la producción de biodiésel a nivel mundial pasará de casi 28 mil millones de litros que se producen en la actualidad, a 38,6 mil millones de litros que se tiene previsto producir en 2014 (García-Camús y García-Laborda, 2006).…”
Section: Introductionunclassified